Prostate Segmentation in MRI Images using Transfer Learning based Mask R-CNN - Shabbir, Maryam; Suhail, Zobia; Hafeez, Nida; Saqib, Najmus; Farooq, Muhammad; Guizani, Sghaier; Rehman, Ateeq Ur; Hamam, Habib (Current Medical Imaging, 2024)
Introduction The second highest cause of death among males is Prostate Cancer (PCa) in America. Over the globe, it’s the usual case in men, and the annual PCa ratio is very surprising. Identical to other prognosis and diagnostic medical systems, deep learning-based automated recognition and detection systems (i.e., Computer Aided Detection (CAD) systems) have gained enormous attention in PCA. Methods These paradigms have attained promising results with a high segmentation, detection, and classification accuracy ratio. Numerous researchers claimed efficient results from deep learning-based approaches compared to other ordinary systems that utilized pathological samples. Results This research is intended to perform prostate segmentation using transfer learning-based Mask R-CNN, which is consequently helpful in prostate cancer detection. Conclusion Lastly, limitations in current work, research findings, and prospects have been discussed.
Keywords: Mask R-CNN